2017
DOI: 10.3390/foods6090080
|View full text |Cite
|
Sign up to set email alerts
|

Polyphenols in Raw and Cooked Cereals/Pseudocereals/Legume Pasta and Couscous

Abstract: Pasta and couscous are popular foods manufactured (in their traditional form) from durum wheat semolina. In recent years, the consumers’ quest for novel, functional, gluten-free, wholegrain foods has prompted the industry to manufacture new pasta and couscous products in which durum wheat has been partially or totally replaced by other vegetable flours. Besides dietary fibre, these raw materials might be an interesting source of phytochemicals. In this work, 16 commercial samples of pasta and four samples of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 22 publications
2
18
0
Order By: Relevance
“…Regarding the present study, the losses of the total phenols content after cooking the fettuccine (around 17-48%) were higher than that reported by Pedrosa et al [16] after the canning process of Almonga bean seeds (by about 11%), but were similar to the results found in the literature in cooked pasta fortified with buckwheat, common and black beans, and red and black lentil pasta [18,43,44]. According to the literature [18,[43][44][45], the reduction in phenols can be attributed to the synergistic combination of several factors, such as the pasta-making process, the sensitivity of heat during the cooking process, the leaching into the broth because of the softening of the food matrix that occurs during pasta cooking, as well as the association with the food matrix during cooking, that might hinder their extraction. Verardo et al [46] reported for cooked buckwheat spaghetti that 11.6% of the different phenolic compounds were dissolved in the cooking water, and the pasta-making process caused a loss of 45.9% of the total phenolic compounds present in the raw materials used in the elaboration of buckwheat spaghetti.…”
Section: Phenolic Composition and Antioxidant Activitysupporting
confidence: 87%
See 1 more Smart Citation
“…Regarding the present study, the losses of the total phenols content after cooking the fettuccine (around 17-48%) were higher than that reported by Pedrosa et al [16] after the canning process of Almonga bean seeds (by about 11%), but were similar to the results found in the literature in cooked pasta fortified with buckwheat, common and black beans, and red and black lentil pasta [18,43,44]. According to the literature [18,[43][44][45], the reduction in phenols can be attributed to the synergistic combination of several factors, such as the pasta-making process, the sensitivity of heat during the cooking process, the leaching into the broth because of the softening of the food matrix that occurs during pasta cooking, as well as the association with the food matrix during cooking, that might hinder their extraction. Verardo et al [46] reported for cooked buckwheat spaghetti that 11.6% of the different phenolic compounds were dissolved in the cooking water, and the pasta-making process caused a loss of 45.9% of the total phenolic compounds present in the raw materials used in the elaboration of buckwheat spaghetti.…”
Section: Phenolic Composition and Antioxidant Activitysupporting
confidence: 87%
“…The reduction ranged from 52% to 82% in the fettuccine without WCF (PC-20.0 and PC-60.0) and from 68% to 86% in the fettuccine with WCF (PC-20.10 and PC-60.10). The decrease was small in the samples with an 80% bean amount, where a reduction of 7% was observed; although the cause of this small reduction remains uncertain, a possible hypothesis is that in these samples, during the pasta-making and cooking processes, a higher amount of phenols are able to bind to the food matrix, which prevents its extraction [44].…”
Section: Phenolic Composition and Antioxidant Activitymentioning
confidence: 91%
“…Laminaria incorporation (either liquor or purée) contributed significantly (p < 0.05) to the protein increase in pasta. The energy value was also lower-Laminaria pastas showed values between 202-207 kcal/100 g (fresh weight), much lower than the energy value (369 kcal/100 g, fresh weight) reported for semolina pasta with Undaria pinnatifida [21], and 310-361 kcal/100 g for commercial GF dry pasta [45,48].…”
Section: Physicochemical Analysis Of Pastamentioning
confidence: 63%
“…Prabhasankar et al [69] also notes that phenolics, in the cooked control semolina pasta, were not significantly different from samples supplemented with Sargassum marginatum. However, in some cases, phenolics in cereal products are reported to increase with cooking, as the process can soften the hard structure and break cellular components, allowing an easier extraction from the matrix [23,48].…”
Section: Effect Of Laminaria Processing On the Presence Of Phytochemimentioning
confidence: 99%
“…To further address this question, future studies should explore NA biofortification within plant foods that contain high endogenous NA levels and low Fe:polyphenol molar ratios (e.g., 1:2 in carioca beans) [21]. Nonetheless, plant species with inherently low polyphenol levels (i.e., wheat) serve as ideal candidates for enhanced Fe bioavailability through the overproduction of NA [26,49]. The additional role of NA in the biosynthesis of DMA (itself an enhancer of Fe bioavailability) further reinforces increased NA biosynthesis as an effective cereal biofortification strategy to improve global human Fe nutrition.…”
Section: Discussionmentioning
confidence: 99%